Decentralization and implementation of climate change policy in Uganda - Friis-Hansen, Esbern; Bashaasha, Bernard; Aben, Charles (DIIS Working Paper, 2013)
The focus of climate change policies and action in Africa south of the Sahara differs from the global agenda. While most debate within the United Nations Framework Convention on Climate Change relates to assessing physical climate change and mechanisms for mitigation, the main concern of most African countries is how to adapt to the effects of climate change. A growing number of projects addressing climate change adaptation and government are formulating new policies that seek to provide a framework to guide these activities. Yet, discussion of the content of and driving forces behind climate change adaptation in national policies has been limited. Even less is known about how such national climate change policies have been implemented and their institutional setting within the country. This working paper explores the driving forces behind the formulation of climate change policies in Uganda and assesses its content and implementation modalities. The working paper explores the extent to which there is a gap between policy and practice at the district and local levels.
Keywords: Decentralization; Climate change policy; Uganda